756 'predicted sickness absence from employment compared with department of social protection guidelines for closed certification with common health problems'. (24th April 2018) - Kononenko, N; Loftus, E; Whelan, D
Abstract : Introduction: Prolonged absence from work may cause deterioration in the patient's health and wellbeing and threaten job security. The Department of Social Protection issued Guidelines for Closed Certification in September 2015 to assist medical certifiers of sickness absence. These Guidelines have been complied for use in an Irish context with regard to evidence-based protocols on various health problems, which were developed by DSP, and also with reference to the Official Disability Guidelines 2013, to The Medical Disability Advisor: Workplace Guidelines for Disability Duration 2009. Methods: This was an observational study. A questionnaire survey emailed to Consultants and HST trainees of different specialties to explore their opinion on predicted duration of sickness absence with different medical conditions and interventions. 71 Consultants and HST trainees from different Medical Specialties and 32 Consultants and HST trainees in Occupational Medicine responded to a survey. The response rate was 29% from Medical Specialists and 44% from Occupational Medicine Specialists. Results: According to this survey 60% of Physicians and 44% of Occupational Health Physicians are not familial with Closed Certification Guidelines. Medical specialist's opinion coincides with Guidelines in 4%–93%, Occupational Medicine Specialists in 4%–100%. The agreement with Guidelines is in responses about less serious (infectious) conditions in both groups, disagreement with Guidelines in responses about more serious medical conditions (cardiac, pneumonia, asthma). There is a trend to predict shorter time for recovery then recommended by Guidelines in both groups. There is no significant difference in predicted absence agreed with Guidelines recommendations among two groups. Discussion: This study compared the opinion of specialists in predicting duration of sickness absence with durations laid down in 'Closed Certification Guidelines for General Practitioners' Not all clinician's opinion coincides with recommended by Closed Certification Guidelines. More than half of participants were not aware about Closed Certification Guidelines.